Addressing Anti-Motivation Issues in a Fifth Basic EFL Educational Learning Environment at Unidad Educativa Politécnico. - Lemos Toalongo, Anggie Lilibeth (2016)
The purpose of this research project is to identify the factors that demotivate students during the teaching-learning process and devise strategies to help both the educator and the learner to deal with such situations when they arise in the classroom. After the pertinent research labor and the review of the literature were completed, it was concluded that in order to get students motivated within their own environment this could be achieved more efficiently through a diverse pedagogical techniques.